Harnessing Virtual Reality For Geoscience Education: Unveiling The Pedagogical Potential Of Ijen Crater's Volcanic Landscape - Ari Hendriansyah, Rizki; Alfyananda Kurnia Putra (Pusat Data dan Teknologi Informasi Kementerian Pendidikan Kebudayaan, Riset dan Teknologi, 2025)
Virtual Reality systems in geography education are generally limited to 3DoF, allowing only rotational movement without translation. This study aims to develop an innovative 6DoF VR learning media using Unity to simulate volcanic processes, ecosystems, and disaster mitigation in the Ijen Crater. The “KawahIjen” VR is designed to provide an immersive and interactive learning experience, overcoming the limitations of conventional media. The research employs a Research and Development (R&D) method, adapting the Hannafin and Peck model, which includes needs analysis, design, development, and implementation stages. Results show the VR has a high usability level, with a System Usability Scale (SUS) score of 81. The 6DoF feature allows users to interact with and explore the virtual environment freely, offering deeper learning experiences. Additionally, it serves as a potential educational tool for disaster mitigation, especially for remote communities with limited access to Ijen. This study contributes to innovative and effective geoscience learning media development. Sistem VirtualReality dalam pendidikan geografi umumnya masih berbasis 3DoF, yang hanya memungkinkan rotasi tanpa translasi. Penelitian ini bertujuan mengembangkan media pembelajaran VR 6DoF inovatif menggunakan Unity untuk mensimulasikan proses vulkanik, ekosistem, dan mitigasi bencana di Kawah Ijen. VR